0
$\begingroup$

I am trying to find an integrating factor for my differential equation \begin{equation} \left( c + \frac{1}{1-z}\right)g(z) + \frac{dg}{dz}\left(\frac{a}{1-z}z - 1\right)+\frac{a}{1-z} z\frac{df}{dz}=0 \end{equation} A similar equation uses $$ (1-z)e^{c z} $$ however, I am struggling to solve this equation. Note that $f(z) = \sum_k e^{c(z-1)} z^k$ such that $$ z\frac{df}{dz} = z(cz-1)e^{c(z-1)} $$ There is no relation between $g$ and $f$.

$\endgroup$
  • $\begingroup$ What's relation between $f$ and $g$ ? $\endgroup$ – Nosrati Aug 10 '18 at 15:15
1
$\begingroup$

Hint: Use $e^{-cz}$ and after multiplying let $h=e^{-cz}g$ to simplify equation.


Edit: $$\left( c + \frac{1}{1-z}\right)g(z) + \frac{dg}{dz}\left(\frac{a}{1-z}z - 1\right)+\frac{a}{1-z} z\frac{df}{dz}=0$$ $$\left( c + \frac{1}{1-z}\right)g(z) + \frac{dg}{dz}\left(\frac{a}{1-z}z - 1\right)+\frac{a}{1-z} z(cz-1)e^{c(z-1)}=0$$ $$c(1-z)g + g + azg' - (1-z)g' + az(cz-1)e^{c(z-1)}=0$$ $$(1-z)(cg-g') + g + azg' + az(cz-1)e^{c(z-1)}=0$$ $$-(1-z)(-ce^{-cz}g+e^{-cz}g') + e^{-cz}g + aze^{-cz}g' + az(cz-1)e^{-c}=0$$ $$-(1-z)(e^{-cz}g)' + (e^{-cz}g) + aze^{-cz}g' + az(cz-1)e^{-c}=0$$ $$-(1-z)h' + h + aze^{-cz}(e^{cz}h'+ce^{cz}h) + az(cz-1)e^{-c}=0$$ $$-(1-z)h' + h + azh' + azch + az(cz-1)e^{-c}=0$$ $$(az+z-1)h' + (azc+1)h + az(cz-1)e^{-c}=0$$ $$h' + \dfrac{azc+1}{az+z-1}h = -\dfrac{az(cz-1)e^{-c}}{az+z-1}$$ let $p=\dfrac{azc+1}{az+z-1}$ with integrating factor $$I=e^{\int p dz}=e^{\frac{ac}{1+a}z}\left(1-(a+1)z\right)^{\frac{1+a+ac}{(1+a)^2}}$$ then $$h(z)=\dfrac{1}{I}\int\left(-\dfrac{az(cz-1)e^{-c}}{az+z-1}\right)I\ dz+C$$ or $$\color{blue}{g(z)=e^{cz}\dfrac{1}{I}\int\left(-\dfrac{az(cz-1)e^{-c}}{az+z-1}\right)I\ dz+C}$$ is the final answer. I think you would better to solve the last integral with online softwares.

$\endgroup$
  • $\begingroup$ Just do as I said. The equation will be of the form $$(az-z+1)h'+(acz+1)h+\cdots$$ $\endgroup$ – Nosrati Aug 10 '18 at 19:03
  • $\begingroup$ Thank you for your help, I will try to do this tomorrow, I really appreciate your time :) $\endgroup$ – AngusTheMan Aug 10 '18 at 21:06
  • $\begingroup$ Thank you for your edit! If I have a condition on $g(1)=1$, do you have any advice on how I can choose the boundary for my integration? $\endgroup$ – AngusTheMan Aug 12 '18 at 18:52
  • $\begingroup$ such as in this question math.stackexchange.com/questions/2880207/… $\endgroup$ – AngusTheMan Aug 12 '18 at 18:53
  • 1
    $\begingroup$ You are welcome. about your question, you may write $$\int_1^w I\ h\ dz=\int_1^w -\dfrac{az(cz-1)e^{-c}}{az+z-1} I\ dz$$ without constant $C$. $\endgroup$ – Nosrati Aug 12 '18 at 18:57

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.